Analisis Pengaruh Tata Kelola Perusahaan terhadap Tanggung Jawab Sosial Perusahaan di Bursa Efek Indonesia - Anita Anita; Lasma Krisna Monika (Universitas Internasional Batam, 2021)
Every company must have social responsibility for its company, because the company must have responsibility for its environment or society with the aim of being able to develop the environment for the process of economic development. In this study, the method used is purposive sampling because the samples taken have certain criteria taken on the Indonesia Stock Exchange from 2015-2019, the model used is the Fixed Effect Model (FEM). The results of this study are board size and firm size have no significant effect on social responsibility. Board independence, leverage, and type of industry have a significant negative impact on social responsibility. Gender diversity and profitability has a significant positive effect on social responsibility.